Quel avenir pour les archives du ministère de la Défense ? - Le Maresquier, Erik (Gazette des archives, 1979)

Les généalogistes et les Archives - Wolff, Christian (Gazette des archives, 1979)
Genealogists and archives. Difficultes encountered and examples of solutions adopted by several archive institutions to meet the increasing number of genealogists. The growing importance of this category of researchers and the risks which they inflict on the preservation of documents make it advisable that archivists adopt a common attitude in their relations with genealogists. Better organisation and discipline of genealogists themselves would make these relations easier.

Missions impossibles ? - René-Bazin, Paule; Prax, Hélène (Gazette des archives, 1978)
The relations between the Archives nationales and the Ministries have been entrusted since 1950 to archivists of the Archives nationales with either a permanent or a parttime mission. Since 1967, these relations are also entrusted to the Cité des Archives contemporaines (Intermediate repository) of Fontainebleau. Archivists in charge of the missions describe the organisation of their work and propose some regulatory and technical improvements.

Le déménagement des Archives départementales de l'Aisne - Souchon, Cécile (Gazette des archives, 1978)

Archives et géologie appliquée. Séismes, glissements, éboulements, érosion anthropique - Vogt, J. (Gazette des archives, 1977)

Manuel d'archivistique. Théorie et pratique des Archives publiques en France - Association des archivistes français (AAF) (1970)

Les cadres de classement réglementaires des archives départementales et communales : essai d'adaptation - Pérotin, Yves (Manuel d'archivistique. Théorie et pratique des Archives publiques en France, 1970)

Réglementations particulières concernant les versements dans les archives départementales - Rigaud, Jacques (Manuel d'archivistique. Théorie et pratique des Archives publiques en France, 1970)

L'acquisition et l'archivage de la «Couverture photographique aérienne I.G.N. » d'un département - Wilsdorf, Christian (Gazette des archives, 1970)